Renewable Energy Sources in the New Industrial Revolution: World and Domestic Experience - S. R. Bekulova (Мир новой экономики, 2019)
The article is devoted to determining the place of renewable energy sources (RES) in the new industrial revolution. The peculiarity of the Fourth industrial revolution, unlike the previous ones, is a particular account of the anthropogenic impact of human activities on the environment. One of the ways to reduce carbon dioxide emissions into the atmosphere is the use of renewable energy technologies. In the article, the author outlined the prerequisites and prospects for the development of renewable energy in Russia and the world, as well as considered the world and domestic experience in the use of renewable energy. On this basis, the author concluded that it is expedient to develop renewable energy sources in Russia. Besides, the author showed that the development of renewable energy technologies could act as a driver of innovative modernisation of the economy and a source of formation of a low-carbon (green) economy characterised by high energy efficiency, energy independence and minimal impact on the environment.